Efikasi diri guru, pemahaman tentang karakter siswa, dan pemahaman tentang keterampilan Abad ke-21 sebagai prediktor gaya mengajar tipe fasilitator - Sa'pang, Aditya Wiranata; Purbojo, Rijanto (Jurnal Psikologi Ulayat: Indonesian Journal of Indigenous Psychology, 2020)
This study aims to examine the effect of teachers’ self-efficacy, their understanding of student characteristics (known as generation Z), and their understanding of the 21stcentury skills towards facilitator teaching style at Dian Harapan School Jakarta. This study used a quantitative approach with 60 respondents. Data was collected using questionnaire, which comprises the Teachers’ Sense of Efficacy Scale, the characteristics of generation Z Students, West Virginia 21st Century Teaching and Learning Survey, and Teaching Style Survey. Data analysis and hypothesis testing were conducted through multiple linear regression analysis and the F Test. The results showed that teachers’ self-efficacy, teachers’ understanding of the generation Z students’ characteristics, and their understanding of the 21st century skills contribute 60.7% on teachers’ facilitator style of teaching. It was concluded that these three factors have an important role on teachers’ facilitator style of teaching.